Las problemáticas psicosociales en Medellín: una reflexión desde las experiencias institucionales (2009)
ABSTRACT: The reflections around the experiences of psychosocial intervention, organized by the working of Mental Health of the National School of Public Health of the University of Antioquia during the years 2003 and 2004, with 93 organizations and institutions of public and private nature, attributed to the educational, social and community, health and ecclesiastical sectors, they allowed to know and to understand the concepts of the psychosocial intervention, the theoretical foundations, the work focuses and problems prioritized on those that base the work psychosocial. The qualitative methodology of the study, was guided under a hermeneutic focus, transcribing and analyzing the stories obtained in the focal groups of five seminars-workshop.